TINDAK PIDANA KEKERASAN TERHADAP PASANGAN YANG BELUM DICATAT DALAM AKTA PERKAWINAN DITINJAU DARI HUKUM POSITIF DI Indonesia - Devis Buni Lele; Jimmy Pello; Aksi Sinurat (to-ra, 2020)
Abstract Violent offenders in scope couples who have been living together in one house whose name not noted in the deed marriage .Formulation problems this research namely whether it is violence which happens to couples have lived together in one house whose name not noted in the deed marriage , is a form of crimes domestic violence or crimes persecution ?The research uses research juridical law normative with the data secondary .The results of the study showed that couples violence in pairs have lived with whose name not noted in the deed marriage in in the form of crimes persecution (Art 351 KUHP). Keywords: Violent Felonies, Couples Who Have Recorded In A Marriage Certificate